How to solve this expression? `(5/6)^(-3)[(5/6)^(3)-:(36/25)^(-2)]^(3){-[(-6/5)^(2)]^(-4)}^(3)= ?` Good morning, how do you solve this expression? thank you!
- print Print
- list Cite
Expert Answers
calendarEducator since 2012
write1,291 answers
starTop subjects are Math and Science
`(5/6)^(-3) [ (5/6)^3 -: (36/25)^(-2) ]^3 { -[(-6/5)^2]^(-4)}^3`
Simplify the expressions inside the braces, brackets and parenthesis. To do so, start from the innermost expression going outside.
Let's start to simplify the expression inside the braces.
>> `{ - [ (-6/5)^2]^-4 } ^3`
Since the power of (-6/5)^2 is an even number , the resulting sign is positive. And use the property of exponents which is `(a^m/b^n)^k = a^(m*k)/b^(n*k)` to simplify.
` { - [6^2/5^2]^-4}^3`
Again, use the property `(a^m/b^n)^k = a^(m*k)/b^(n*k)` .
` { - 6^(2(-4))/5^(2(-4)) }^3 = {-6^(-8)/5^(-8) }^3`
Since the outermost power is an odd number, the resulting sign of the expression inside the braces is negative and apply the same property of exponents.
`-6^(-8*3)/5^(-8*3) = - 6^(-24)/5^(-24)`
So we have,
`=(5/6)^(-3)[(5/6)^3 -: (36/25)^(-2)]^3 *(-6^(-24)/5^(-24))`
Next, simplify the expression inside the brackets.
>> `[(5/6)^3 -: (36/25)^(-2)}^3`
Express 36 as `6^2` and 25 as `5^2` .
`[ (5/6)^3 -: (6^2/5^2)^(-2) ]^3`
Apply the exponent property `(a^m/b^n)^k = a^(m*k)/b^(n*k)` .
`[ 5^3/6^3 -:6^(2(-2))/5^(2(-2)) ]^3 =[ 5^3/6^3 -: 6^(-4)/5^(-4)]^3`
To divide fractions, flip the divisor and change the operation from division to multiplication.
`[5^3/6^3 * 5^(-4)/(6^(-4))]^3 = [(5^3*5^(-4))/(6^3*6^(-4))]^3`
To multiply same base, add the exponents.
`[5^(3+(-4))/6^(3+(-4)) ]^3 = [5^(-1)/6^(-1)]^3 = 5^(-3)/6^(-3)`
So we have,
`= (5/6)^(-3) *5^(-3) / 6^(-3)* (-6^(-24)/5^(-24)) = 5^(-3)/6^(-3) * 5^(-3)/6^(-3) * (- 6^(-24)/5^(-24))`
`= -(5^(-3) * 5^(-3) * 6^(-24))/(6^(-3)*6^(-3)*5^(-24)) = -(5^((-3)+(-3)) * 6^(-24))/(6^((-3)+(-3))*5^(-24)) =-(5^(-6)*6^(-24))/(6^(-6)*5^(-24))`
To divide same base, subtract the exponents `(a^m/a^n = a^(m-n))` .
`=-5^(-6-(-24)) 6^((-24)-(-6)) =- 5^18*6^(-18)`
To express 6 with positive exponent, apply the negative exponent rule which is `a^(-m)= 1/a^m` .
`= -5^18/6^18`
Hence, `(5/6)^(-3) [ (5/6)^3 -: (36/25)^(-2) ]^3 { -[(-6/5)^2]^(-4)}^3 = -5^(18)/6^(18)` .
Related Questions
- 5/6·1/2+2/3÷4/3 How do I solve this problem?
- 1 Educator Answer
- Solve for x 25^x - 6*5^x + 5 = 0.
- 1 Educator Answer
- How do I solve 6 3/4 + 1 5/6?
- 2 Educator Answers
- `5^(x-4)=25^(x-6)` Solve the equation.
- 1 Educator Answer
- What is the result of the following using BODMAS: a)3 x (10+5) + (48/6)/4 - 7 b)3 + 4x6 - 8 c)6 -...
- 1 Educator Answer